ANALISIS NOVEL RE: KARYA MAMAN SUHERMAN BERDASARKAN PENDEKATAN FEMINISME - Oktavia Utami, Putri; Kusyani, Diah; -, Arianto (Jurnal Bahasa Indonesia Prima (BIP), 2024)
Feminism comes from the Latin femina or woman. The term began to be used in the 1890s, referring to the theory of equality between men and women and the movement to obtain women's rights. This research uses a library research design. The subject of this research is the novel Re: by Maman Suherman. The object of research is feminism found in the novel Re: by Maman Suherman. Important data will be the subject of this research is marked and recorded to be grouped according to feminism, and the struggle of Re: which will be researched. This study found that there are 1 aspect that discusses feminism which is described as part of the right to freedom, 1 aspect that discusses the struggle in the field of education, 0 aspects that discuss the struggle in civil rights, 2 aspects that discuss the struggle in the economic field, 8 aspects that discuss the struggle in the right to express opinions, and 5 aspects that discuss the struggle in the right to assemble. This research aims to describe the study of feminism and describe the struggle of Re: in realizing feminism in the novel Re: by Maman Suherman. As a literary work, novels can be used as a lesson. One of the novels that can be used as learning is the novel Re: by Maman Suherman, which can be utilized to add insight into feminism. This novel can be implied by providing sexual direction or learning from an early age, because the counseling can be used as a guide so that unwanted things do not happen.